Penguatan Kapasitas SDM Desa Wisata Bojong: Integrasi Growth Mindset dan Benchmarking ke Desa Pentingsari - Rustiana; Anna Pudianti; Boy Rahardjo Sidharta; Felix Adi Wibowo; Raynold Steven Simamora (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
This community service program aimed to strengthen the human resource capacity of tourism village administrators of Bojong Tourism Village through the development of a growth mindset integrated with a benchmarking visit to Pentingsari Tourism Village, Sleman. The program, conducted on July 26, 2025, involved 19 prospective tourism village administrators, consisting of 12 men and 7 women. The benchmark was designed through four main stages: (1) outbound activities; (2) a sharing session with Pentingsari managers on strategies for tourism village development and the formulation of a unique selling point; (3) participation in local attractions, namely the gamelan-playing experience and Merapi honey coffee educational tour; and (4) filling of a growth mindset questionnaire before the activities. The results indicated increased awareness among participants regarding the importance of continuous learning, creativity, collaboration, spontaneous leadership, and communication skills in tourism village management. These findings highlight that integrating growth mindset and benchmarking can serve as an effective strategy to strengthen human resource capacity, foster innovation, and promote sustainability in the development of Bojong Tourism Village. Keywords: growth mindset, benchmarking, tourism village, integration